La ansiedad en mujeres autistas de 14 a 21 años: un estudio cualitativo - Mesones Rosemberg, Andrea (2022)
The purpose of this research is to explore and describe how autistic women live anxiety. In order to accomplish this, the objectives of the research aim to present how does they experience it, their triggers and their coping strategies. The research has a qualitative approach, with an exploratory and descriptive scope following a phenomenological method and specially giving the relevance to the experiences of the interviewed women. The sample used was composed of women within the Autistic Spectrum Condition between 14 and 21 years old while the data was gathered through semi structured interviews. The results showed that the triggers of anxiety found were the unexpected changes, the overdemand, the social media and others. The anxiety experience in autistic women involves typical and atypical manifestations; within atypical manifestations, common components emerged like camouflage, self-demand and stereotypes. The impact of the anxiety affects in their personal relationships and the execution of their daily activities. this was linked with the limitation that anxiety brings to their daily activities. Finally, some of the coping strategies found were activities related to their interests, regulation movements, support network and anticipation actions for specific situations.